Additional Manufactured Interim Restorations: a Review on the Literature - Marzieh Alikhasi; Zahra Jafarian (Shiraz University of Medical Sciences, 2022)
Interim restorations are essential in many clinical scenarios in which indirect restorations are administered. Additional manufacturing (AM) technology has recently been introduced and applied in different fields of dental practice. This study aimed to collect relevant information from published papers regarding different aspects of AM temporary restorations with a focus on the most relevant technical properties. An electronic search was performed on Medline/ PubMed/ Scopus databases up to April 2020 to find relevant, peer-reviewed articles about AM provisional restoration. Although promising results for AM temporary restorations were obtained, comprehensive application of this technology in making provisional restorations requires information to address the missing properties concerning the short time of application.